2014
DOI: 10.1002/eji.201444538
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal B‐cell antigen receptor signaling activity in vivo elicits germinal center counterselection mechanisms

Abstract: Keywords: BCR r GC r Interclonal competition r Syk r Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionThe investigation of activation processes triggered by the B-cell antigen receptor has kept the scientific community busy for many years, in particular, understanding the spatial BCR organization Correspondence: Dr. Friedemann Kiefer e-mail: fkiefer@gwdg.de and the orchestration of kinase/phosphatase activity on resting versus activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The above points provide a mechanistic explanation for the enhanced activation of B cells on softer but not stiffer PDMS substrates, which we believe might also explain the similar observation in T cells. Moreover, the very recent BCR signaling pathway studies by Reth and his colleagues showed that cre-mediated Syk deletion in Sykflox/Zap-70 mouse primary B cells lowered the phosphorylation of Erk signaling molecule, but not the phosphorylation of Akt-mediated signaling, suggesting that Syk activation and Akt are not necessarily coupled signaling modulus in B-cell activation [41]. The contemporary data in this report echo back the early pioneer studies by Mond and Dintzis and their colleagues showing that anti-Ig (anti-IgM antibody as surrogate antigen) conjugated to dextran will be 1000-fold more potent to drive in vitro B-cell expansion than unconjugated soluble anti-Ig [42], suggesting that stiffness feature of the substrates presenting the antigens would dramatically affect the mutagenicity of these antigens to drive B-cell expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above points provide a mechanistic explanation for the enhanced activation of B cells on softer but not stiffer PDMS substrates, which we believe might also explain the similar observation in T cells. Moreover, the very recent BCR signaling pathway studies by Reth and his colleagues showed that cre-mediated Syk deletion in Sykflox/Zap-70 mouse primary B cells lowered the phosphorylation of Erk signaling molecule, but not the phosphorylation of Akt-mediated signaling, suggesting that Syk activation and Akt are not necessarily coupled signaling modulus in B-cell activation [41]. The contemporary data in this report echo back the early pioneer studies by Mond and Dintzis and their colleagues showing that anti-Ig (anti-IgM antibody as surrogate antigen) conjugated to dextran will be 1000-fold more potent to drive in vitro B-cell expansion than unconjugated soluble anti-Ig [42], suggesting that stiffness feature of the substrates presenting the antigens would dramatically affect the mutagenicity of these antigens to drive B-cell expansion.…”
Section: Discussionmentioning
confidence: 99%
“…The above points provide a mechanistic explanation for the enhanced activation of B cells on softer but not stiffer PDMS substrates, which we believe might also explain the similar observation in T cells. Moreover, the very recent BCR signaling pathway studies by Reth and his colleagues showed that cre‐mediated Syk deletion in Sykflox/Zap‐70 mouse primary B cells lowered the phosphorylation of Erk signaling molecule, but not the phosphorylation of Akt‐mediated signaling, suggesting that Syk activation and Akt are not necessarily coupled signaling modulus in B‐cell activation .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, bone marrow-derived pHSCs give rise to shorter-lived BIb cells, which have homing properties that are similar to BIa cells. Most importantly, bone marrow develops BII-type B lymphocytes, which organize the B cell follicles in spleen and lymph nodes (85,86 Any high-affinity, autoreactive B cells that emerge as accidental products of the hypermutation process during this affinity maturation of better-fitting antibodies should be silenced and eliminated to avoid autoimmune disease (89)(90)(91)(92). Again, the microenvironments mediating this postulated negative selection of autoantibodies need further investigation.…”
Section: Establishment Of Peripheral Pools Of Mature B Cellsmentioning
confidence: 99%